Research on the spatiotemporal evolution of deformation and unloading mechanical effects in underlying coal and rock during upper protective layer mining - Lei, Wulin; Chai, Jing; Zheng, Chao; Zhao, Jian; Wang, Siyang; Liu, Guixian; Zhang, Jufeng; Yang, Rili (Frontiers in Earth Science, 2025)
The spatiotemporal rule of pressure release in rock–coal strata within the mining zone serves as the theoretical basis for the prevention and control of dynamic disasters during the mining of the stress-concentration stratum. Taking the mining of the upper protective layer of the Hulusu coal mine located in Ordos City, Inner Mongolia Autonomous Region, China, as the engineering background, this study, based on the theory of elastic–plastic mechanics, investigates the pressure relief mechanics of the underlying coal and rock during the upper protective layer mining. The research is conducted across different scales through rock mechanics experiments, numerical simulations, and on-site industrial experiments. The spatiotemporal evolution of the stress and displacement fields in the underlying coal and rock strata during the upper protective layer mining was simulated and analyzed using the 3-Dimensional Distinct Element Code. Brillouin optical time-domain analysis distributed fiber-optic sensing technology was used to monitor the deformation and unloading dynamic process of different rock–coal strata under the mining floor in real-time. The results indicate that the stress changes in the underlying rock–coal strata during the mining of the upper stress-concentration stratum can be divided into four phases, namely, in situ stress, stress concentration, stress release, and stress restoration. Due to the uneven distribution of the waste rock collapse in the mined-out area, stress is alternately distributed in the unloading stable zone, unloading recovery zone, and boosting zone. The mining-induced stress distribution curve in the protected coal seam changes from a U-shape to a W-shape and then to a “WWW”-shape. The stress-relieving effect of upper stress-concentration stratum mining is significant, but the stress-relieving parameters vary depending on time and spatial factors. The research results have important theoretical and practical significance for guiding the layout and key parameter design of stress-concentration stratum mining.